Effects of Cd2+ substitution on elastic properties and step-like anomalies in Tl0.9Bi0.1Sr1.8Yb0.2Ca1−xCdxCu1.99Fe0.01o7−δ superconductors. (June 2015) - Ismail, S.; Ibrahim, Abdel-Baset M.A.; Yahya, A.K.
Abstract: Cd-doped Tl0.9 Bi0.1 Sr1.8 Yb0.2 Ca1− x Cd x Cu1.99 Fe0.01 O7− δ ( x =0–0.4) bulk superconductor samples were prepared by solid-state reaction method, to examine the effect of Cd on ultrasonic velocity and elastic behavior of the samples. The samples were characterized by X-ray diffraction, DC electrical resistivity and temperature dependent ultrasonic velocity measurements. DC electrical resistivity measurement showed all the samples exhibit metallic normal-state behavior with the highest T c zero observed at around 76.4 K ( x =0.3). Ultrasonic velocity measurements at 80 K showed a non-linear increase in both absolute longitudinal and shear velocities as well as elastic moduli with Cd substitution with the largest increase observed for the x =0.3 sample. Temperature dependant longitudinal modulus showed elastic anomaly characterized by a step-like slope change at around 230 K for x =0 & x =0.3 and at around 250 K for x =0.4 with the x =0.3 sample showing the sharpest slope change. A comparison between experimental data and calculated lattice anharmonicity curve based on the model proposed by Lakkad, showed large deviation of the experimental longitudinal modulus curves for ( x =0.3) from the calculated anharmonicity curves indicating that the elastic behavior was strongly influenced by the existence of the step-like longitudinal anomaly. On the other hand, our analysis using the Landau free energy model found that the anomalous step-like elastic behavior fitted well with the equation derived from the model for regions below and above the elastic anomaly temperature, T A . The fitting indicated that the anomaly is related to a phase transition that is suggested to involve ordering of oxygen which introduces strain in the system. Highlights: Elastic properties of Tl0.9 Bi0.1 Sr1.8 Yb0.2 Ca1-x Cdx Cu1.99 Fe0.01O7-δ ( x = 0-0.4) superconductors were investigated by ultrasonic velocity measurements. Elastic anomaly was observed around 230–250 K with the sharpest anomaly observed at x =0.3. The anomaly was fitted well to the Landau model indicating a phase transition which is suggested to involve oxygen ordering. Elastic moduli and Debye temperature, θ D showed maximum values for the x =0.3 sample which also displays the highest T c zero .